PENDIDIKAN BIOLOGI BERBASIS IMTAQ SEBAGAI USAHA PEMBENTUKAN KARAKTER BANGSA - Milya Sari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2013)
Indonesia's education system hasn't been able to reflect the learners and educational output character. One cause is the paradigm the teacher who assumes coaching Morals as the character formation of students in the school as a teacher of religious education task. Coaching these characters could be done by science teachers particularly biology, according to the purpose of the first biological subjects. Biology teacher responsible for teaching the values of Islam (imtaq) in the material he teaches. To cultivate ketaqwaannya, then all learner activities; think, feel, behave, and act responsibly (BMB3) will be based on the values ketaqwaan. This will form the learners character illustrated in appearance everydayKata kunci: Pendidikan biologi. Pendidikan karakter, Imtaq dan iptek